Enhancement of polyhydroxyalkanoate production by Priestia aryabhattai ML113 isolated from Me Linh, Hanoi - Nguyen, Kim Thoa; Lai, Thi Hong Nhung; Phan, Thi Tuyet Minh; Nguyen, Van Nam; Hoa, Thi Minh Tu; Tran, Thanh Thuy; Nguyen, Quoc Viet; Nguyen, The Trang; Do, Thi Thanh Trung; Le, Tat Thanh (Vietnam Journal of Biotechnology, 2025)
Polyhydroxyalkanoates (PHAs) are biodegradable polyesters that microorganisms naturally accumulate as intracellular carbon and energy reserves. They are considered environmentally friendly alternatives to petroleum-based plastics. This study evaluated Priestia aryabhattai ML113 for its ability to synthesize PHA and employed a two-step optimization strategy to enhance polymer yield. In the preliminary one-factor-at-a-time (OFAT) experiments, temperature, fermentation time, and the carbon-to-nitrogen (C/N) ratio were identified as the most influential factors, yielding a maximum PHA concentration of 1.16 g L⁻¹ under conditions of 35°C, 72 h, and a C/N ratio of 28:1. Subsequently, response surface methodology (RSM) using a Box–Behnken design (BBD) was applied to analyze factor interactions and quadratic effects. The developed regression model predicted an optimal PHA concentration of 1.3014 g L⁻¹, achieved under 34°C, 72 h, and a C/N ratio of 30:1. Experimental validation confirmed a comparable yield of 1.4473 ± 0.03 g L⁻¹, corresponding to a 1.25-fold improvement compared with the OFAT result. The strong correlation between predicted and observed values confirms the model’s reliability. It highlights the effectiveness of integrating OFAT screening with RSM optimization as a scalable strategy for improving PHA biosynthesis. This study represents the first systematic optimization of PHA production by P. aryabhattai ML113, providing a methodological framework for exploiting this strain and low-cost carbon sources toward sustainable bioplastic production.